PROTECTIVE EFFECT OF IRIS GERMANICA L. IN Β-AMYLOID-INDUCED ANIMAL MODEL OF ALZHEIMER’S DISEASE - Borhani, Mona; Sharifzadeh, Mohammad; Farzaei, Mohammad Hosein; Narimani, Zahra; Sabbaghziarani, Fatemeh; Gholami, Mahdi; Rahimi, Roja (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Alzheimer’s disease (AD) is the most common cause of dementia that is an irretrievable chronic neurodegenerative disease. In the current study, we have examined the therapeutic effects of Iris germanica extract on Amyloid β (Aβ) induced memory impairment. Materials and Methods: Wistar rats were divided into five groups of 8 per each. Groups were as followed: control group which were normal rats without induction of AD, Aβ group which received Aβ (50 ng/side), iris 100 group which received Aβ + Iris (100 mg/kg), iris 200 group which received Aβ + Iris (200 mg/kg), and iris 400 group which received Aβ + Iris (400 mg/kg). AD was established by intrahippocampal injection of 50 ng/μl/side Aβ1-42. The day after surgery, animals in treatment groups received different doses of the aqueous extract of Iris by gavage for 30 days. Morris water maze test (MWM) was performed to assess the effects of I. germanica on learning and memory of rats with Aβ induced AD. Results: Data from MWM tests, including escape latency and traveled distance, demonstrated that I. germanica extract could markedly improve spatial memory in comparison to control. Moreover, the plant had a significantly better effect on the performance of AD rats in the probe test. Conclusion: I. germanica extract can successfully reverse spatial learning dysfunction in an experimental model of AD. Further neuro psyco-pharmacological studies are mandatory to reveal the mechanism of action of this natural remedy in the management of AD symptoms.